2007
DOI: 10.1007/s11082-008-9193-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of gain flatness for multi-channel amplification in single stage EDFA for WDM applications

Abstract: In this paper, gain flatness is studied for simultaneous 16-ITU-T channel amplifications at C-band (1,532-1,558 nm) in a single stage EDFA for WDM application at different average inversion levels. The inversion levels are varied due to the change of the input signal levels from the targeted operating point and also for dropping few numbers of channels. Specially designed gain flattening filter (GFF) is used in order to get the flat gain with gain variation ±0.5 dB for −20 dBm/ch input signal power (total inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
1
1
0
3
Order By: Relevance
“…In our case, flat spectral gain is achieved mainly due the low cross gain modulation effect generated at the DRA gain, which was previously showed that provides flat spectral gain [6], due the constant popUlation inversion at the EDFA AGC stage. Additionally, the DRA amplifIer improves the effective noise figure of the proposed amplifIer due the distributed gain at the transmission span [1].…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…In our case, flat spectral gain is achieved mainly due the low cross gain modulation effect generated at the DRA gain, which was previously showed that provides flat spectral gain [6], due the constant popUlation inversion at the EDFA AGC stage. Additionally, the DRA amplifIer improves the effective noise figure of the proposed amplifIer due the distributed gain at the transmission span [1].…”
Section: Resultssupporting
confidence: 65%
“…This hybrid amplifier considers both amplifier technologies (EDFA and counter-propagating DRA) in a single amplifier structure. The HGC scheme is based on an EDF A with custom designed GFF to provide flat spectral gain for full C-band at the nominal gain [6] which is the lowest gain value from the gain setpoint range. Then for higher setpoint gains, the multi pump DRA on-off AGC provides the remainder gain [5].…”
Section: Methodsmentioning
confidence: 99%
“…A topologia de amplificação óptica EDFA com duplo estágio de amplificação GFF, atenuador óptico variável (VOA), e controle automático de ganho eletrônico realimentado (controle de ganho acoplado) é uma estrutura complexa de amplificação que visa fornecer planicidade espectral de ganho para toda a faixa de ganhos alvos controláveis (Abu Bakar et al, 2011;Mahdi et al, 2009), algo que o amplificador EDFA de estágio simples não é capaz de realizar (Paiva et al, 2012;Pal et al, 2007). do ganho alvo ao longo de toda máscara de potência de operação (Paiva et al, 2012).…”
Section: Edfa Com Estágio Duplo Gff Voa E Agc Eletrônico Realimentaunclassified
“…Considerando a busca por um projeto de EDFA de alto desempenho óptico, nesta tese a topologia de EDFA com bombeio co-propagante e GFF sempre é considerada, devido ao desempenho superior com relação à figura de ruído frente às topologias contrapropagante e bi-direcionais (Pal et al, 2007) • EDF: 5 m a 30 m, com incrementos de 1 m, para as fibras dopadas fornecidas pela OFS c (HP980, MP980 ou R37004, R37003).…”
Section: Metodologia De Projeto Otimizado De Amplificador a Fibra Dopunclassified
See 1 more Smart Citation